Breathers of an ampler day: Victorian views of Heaven - Bradley, Ian C. (Sacristy Press, 2023)
As death comes out of the closet in contemporary society, this book presents the views on heaven and the afterlife of a number of well-known Victorians, and others not so well known, in the belief that they may help us today.